Utility of PET/CT in the approach to the patient with tumor of unknown primary - Ledesma-Vásquez, Richard (2022)
Cancer of unknown primary is an infrequent disease, with high mortality. PET/CT can be a procedure to find the primary tumour and represents an aid in initialmanagement, providing better survival and quality of life in these patients, which mainly come to physicians at an advanced stage of their disease.